Identification and theoretical justification of the core preconditions for the development of digital financial ecosystems - Manoylenko, Oleksandr; Kuznetsova, Svitlana (Technology audit and production reserves, 2026)
The object of research is the process of forming digital financial ecosystems in the context of the transformation of the global financial architecture. The problem is the gaps in the forming digital financial ecosystems during the transformation of the global financial architecture under the influence of technological innovations. This is due to the introduction of blockchain technologies, smart contracts, intelligent agents (based on the introduction of artificial intelligence systems), multi-protocol financial technologies, the lack of unified standards and regulatory norms. A systems approach, structural-functional, comparative and institutional analysis, as well as trend analysis methods serve as the methodological basis of this research, implemented on the basis of statistical data from the Statista database and McKinsey & Company reports. Based on the generalization of quantitative and comparative assessments, the main trends in the transformation of the global financial architecture have been identified and analyzed. Institutional changes in the financial market based on the introduction of decentralized financial technologies (DeFi) and the implementation of the ISO 20022 regulatory standard are systematized. Key barriers to the transformation of modern financial architecture are identified, and directions for overcoming them are highlighted based on the development of hybrid financial solutions, international unification of standards and regulatory norms. The concept of forming a hybrid financial architecture (CeDeFi) and digital financial ecosystems is substantiated, which combines the advantages of decentralization and innovation with the reliability of the traditional financial system. The practical significance of research lies in the possibility of using its results to form effective strategies for the development of digital financial ecosystems, improve regulatory policy and make management decisions by financial institutions and fintech companies.